The hunt for gene dopers - Mansour, M. M. H.; Azzazy, H. M. E. (Drug Testing and Analysis, 2009)
Gene doping, the abuse of gene therapy for illicit athletic enhancement, is perceived as a coming threat and is a prime concern to the anti-doping community. This doping technique represents a significant ethical challenge and there are concerns regarding its safety for athletes. This article presents the basics of gene doping, potential strategies for its detection and the role of promising new technologies in aiding detection efforts. These include the use of lab-on-a-chip techniques as well as nanoparticles to enhance the performance of current analytical methods and to develop new doping detection strategies.